Europeanization of the activities of local and regional governments in Poland - Swianiewicz, Paweł (Journal of Public Governance, 2012)
The paper refers to Börzell and Risse’s concept of top-down Europeanization, which allows to distinguish between three levels of impact: absorption, accommodation and transformation. The main focus is on changes in the activities of Polish local and regional governments, resulting from the access to EU funds. The authors analyze the results of three empirical research projects (related to the implementation of regional operating programmes, urban renewal programmes, and absorption of EU funds available for pre-school education) from the point of view of the impact of EU funds on the administrative structures, the priorities of local and regional policies as well as styles of policy preparation and implementation. The main conclusion is that shallow learning is dominant (absorption level), but there are also instances of deep learning which resemble transformation in Börzell and Risse’s theory.